The Necessity to Calculate the Impact of Climate Risks on Determiningthe Cadastral Assessment of Agricultural Lands - Hovhannisyan, Tigran; Efendyan, Paruyr; Khudaverdyan, Nane (ՀԱԱՀ հիմնադրամ)
Armenia, with its entire territory, is considered the most sensitive country to climate change. The land tax rate for agricultural lands is determined at 15 percent of the estimated net income determined by their cadastral assessment. The cadastral assessment of agricultural lands in the Republic of Armenia was carried out in 2002-2004. During the assessment, the materials of land management, soil science, geobotanical, and other studies and research conducted in the 1970-1980s were taken as a basis. The article presents the results of research and analysis conducted by the authors during 2020-2023, on the impact of climate risks on the yield and quality of crops on agricultural lands in the Republic of Armenia. As a result of the research, it turns out that among climate risks, the greatest damage to agricultural lands in the Republic of Armenia is caused by frost, hail, and drought, which affects the quantity and quality of crops from agricultural lands, and consequently the income received, which, however, does not reduce the tax burden of the landowner. As a result of the research, to modernize the assessment methodology in the process of calculating net income, it is recommended to adopt the revised calculation method developed and proposed by the authors using risk reduction coefficients (climate risks).
Keywords: Agricultural Economics and Agribusiness